Islamic Politics as an Ethical and Moral System in Modern Government - Abid Nurhuda; Ahmad Hadi Pranoto; Ali Anhar Syi’bul Huda; Inamul Hasan Ansori (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2025)
Islamic politics since its conception has by no means been perceived as a power game, yet as a moral tool of achievement of social good (maslahah 'ammah). Islamic politics turned into an ethical system, which links transcendental values and social agreement throughout history. This paper will attempt to unveil the ethical and moral aspects of the Islamic politics through the historical background of the religion, its normative basis, and importance to present day governance, which suffers a crisis of integrity and ethical direction. Classical thinking (Al-Farabi, Al-Mawardi, and Ibn Khaldun) and the practices of the Islamic state, since the Medina Charter to the modern dynamics of Muslim-majority countries, are reread critically-analytically. The discussion indicates that Islamic politics is not just a value system but includes theological ideals but constitutes an ethical system of governance founded on justice, trust, responsibility to the people and shura. In the contemporary world, the values have been used in the fight against corruption, maintenance of good governance and enhancement of moral authority of the state in the backdrop of findings of secularization and crisis of the confidence of the citizens. Islamic politics, thus is not opposite of modern democracy but a morally based foundation of state government which is integrally oriented on human welfare, both on spiritual, social, and political fronts.